Pyogene Spondylodiszitis: Therapiealgorithmus und neue Klassifikation zur therapeutischen Entscheidungsfindung = Pyogenic spondylodiscitis : therapy algorithm and a new classification for therapeutic decision-making - Akbar, Michael; Lehner, Burkhard; Eichler, Markus; Wang, Haili; Wiedenhöfer, Bernd (Der Orthopäde, 2012)
The incidence of pyogenic spondylodiscitis is low but has been steadily increasing in recent years. To date there has been no consensus concerning selection of the appropriate treatment, management and strategies and the recommendations for an operative strategy are still a highly controversial issue. In the literature a few statements have been published concerning therapeutic decision-making in pyogenic spondylodiscitis. The classification given in this article is based on clinical experience and retrospective data analysis considering the degree of segmental bony destruction, grade of kyphosis and instability, epidural involvement of the disease and neurological deficits, which are pivotal for therapeutic decision-making. The therapeutic procedure can be defined based on this classification.